Analysis of the Effect of Economic Growth, Open Unemployment Rate, and Capital Expenditure on Income Disparity - Daya Amarta Suwarjana; Niniek Imaningsih (Politeknik Baubau, 2026)
Income disparity is an important issue in regional development as it reflects inequality in the distribution of welfare across regions or social groups. This study aims to analyze the effect of regional economic growth, open unemployment rate, and regional government capital expenditure on income disparity in Pacitan Regency and Wonogiri Regency during the period 2010–2023. This research employs a quantitative approach using secondary data obtained from the Central Statistics Agency (BPS) of East Java and Central Java Provinces, as well as BPS of Pacitan Regency and Wonogiri Regency. The study population consists of annual socio-economic indicator data, with a total sampling technique of 14 years of observation for each regency. Data analysis is conducted using multiple linear regression with the assistance of IBM SPSS 25 software. The partial test results indicate that the effects of independent variables on income disparity differ between regions. In Pacitan Regency, regional economic growth and open unemployment rate have no significant effect on income disparity, while capital expenditure has a positive and significant effect. Conversely, in Wonogiri Regency, regional economic growth and open unemployment rate have a negative and significant effect on income disparity, whereas capital expenditure has no significant effect. These findings provide policy implications for local governments in designing more equitable and inclusive development strategies.